2016
DOI: 10.1039/c6ce00822d
|View full text |Cite
|
Sign up to set email alerts
|

CS⋯I halogen bonding interactions in crystalline iodinated dithiole-2-thiones and thiazole-2-thiones

Abstract: The propensity of the sp 2 sulfur atom in thiones to act as a halogen bond (XB) acceptor is well established with dihalides (I 2 , IBr or ICl) as XB donors, but has been more rarely explored with organic XB donors. The crystal structures of four iodinated heterocycles, namely, the mono-and diiodo derivatives of 1,3-dithiole-2-thione and N-ethylthiazole-2-thione, offer an opportunity to evaluate the strength and directionality of such C-I⋯S interactions. We describe here the original synthesis of 3-ethyl-5-iodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Simple comparisons with literature data for other types of acceptor sulfur atoms (thione, thiocyanate, or thioamide) show that these halogen bonds feature comparable or slightly higher upper limits on R.S. values (albeit at lower temperatures) to those in this work (6.0–17% for thiones, 43 , 45 , 46 7.6–17% for thioamides, 47 , 48 and 5.8–16.4% for thiocyanate species 39 42 , 57 ), as well as that the more exposed sulfur atoms or ions can participate in multiple halogen and hydrogen bonds. This apparent disadvantage of the hindered cyclic sp 3 sulfur can also be considered an advantage, because it could have less propensity for hydrogen bonding.…”
supporting
confidence: 67%
“…Simple comparisons with literature data for other types of acceptor sulfur atoms (thione, thiocyanate, or thioamide) show that these halogen bonds feature comparable or slightly higher upper limits on R.S. values (albeit at lower temperatures) to those in this work (6.0–17% for thiones, 43 , 45 , 46 7.6–17% for thioamides, 47 , 48 and 5.8–16.4% for thiocyanate species 39 42 , 57 ), as well as that the more exposed sulfur atoms or ions can participate in multiple halogen and hydrogen bonds. This apparent disadvantage of the hindered cyclic sp 3 sulfur can also be considered an advantage, because it could have less propensity for hydrogen bonding.…”
supporting
confidence: 67%
“…Much of the recent XB research on the donor systems has concentrated on nonperfluorinated iodine based XB donors like iodonium (I + ), I 2 , and tetraiodoethylene. , On the XB acceptor side, a large part of the recent XB research has been focused on nitrogen compounds, although other XB applications, such as anion recognition, , have been actively researched and shown to be useful, e.g., as analytical tools. Out of the other possible XB acceptors, neutral sulfur species have attracted relatively little attention, but, for example, two studies on weak XBs of the title thiocarbonyl compounds were recently reported. , …”
Section: Introductionmentioning
confidence: 99%
“…The double C−I···S halogen bonds are the same in structural parameters (Supplementary Table 3), being 3.764(3) Å in length that is shorter than the sum of the van der Waals radii of I and S atoms (3.780 Å) 33 , whereas the angle of the halogen bond is 156.3(3)°, being almost linear. The bond length is longer than the usual I···S contacts, such as those in crystalline iodinated dithiole-2-thiones and thiazole-2-thiones that range from 3.2 to 3.4 Å 27 , but it is comparable to those in the classic crystals of I-substituted tetrathiafulvalene derivatives with I 3 − or I 2 that range between 3.7–3.9 Å 28 . The longer length observed here may result from the balance of the bond lengths and angles, since shorter lengths will lead to smaller angles in the crossed geometry with two I···S contacts.…”
Section: Resultsmentioning
confidence: 84%